A TRIZ-based product-service design approach for developing innovative products. (November 2021) - Chou, Jyh-Rong
Highlights: A TRIZ-based product-service design approach to assist designers/engineers in developing innovative products. Addressing the shifting interest of research and practices in Smart product-service systems (PSS). A new perspective on cyber-physical product design beyond the developing Smart PSS design. A design framework based on the 4 pillars of functionality, serviceability, usability, and sustainability. Developing a novel face mask for use by customers in the context of COVID-19 pandemic. Abstract: As recent ICT-enabled innovations are becoming increasingly popular, there will inevitably be a need for enterprises to create innovative products and services to help improve people's daily lives. Although current product-service systems (PSS) envision a future in coupling products and services to co-create more satisfying value for both customers and enterprises, most recent studies focus on a product's service system design in the context of its use phase rather than a methodical support for implementing entire PSS design. This research aims to address the shifting interest of research and practices in Smart PSS from the viewpoint of product design and development (PDD). It presents a TRIZ-based product-service design approach to assist designers/engineers in developing innovative cyber-physical products (CPP) for use by customers. In the context of COVID-19 pandemic, an empirical study concerning a novel face mask design was conducted to verify the applicability and validity of the proposed design approach. The theoretical frameworks and practical implications of the proposed approach are also discussed.